IMPLEMENTASI SISTEM PAKAR CERTAINTY FACTOR UNTUK ANALISA PENYAKIT SINUSITIS - FahrulRazi (ITB Ahmad Dahlan Jakarta, 2023)
Humans can suffer from a variety of sinusitis types, which can be uncomfortable when engaging in activities. Insufficient understanding of sinusitis illness casts doubt on the diagnosis of sinusitis type. An inflammatory condition called sinusitis affects the mucous membrane of the sinuses, an air-filled chamber in the head that surrounds the nose. It is referred to as maxillary sinusitis if it affects the cheekbones. Ethmoid sinusitis is the name for the one that is situated near the corner of the eye, behind the nose bridge. Frontal sinusitis is the term used to describe the one on the forehead. Spheniodalis sinusitis is the name for the one behind the ethmoid sinus. This paper explains how the Certainty Factor technique is used by the expert system to diagnose sinusitis. The Certainty Factor approach is used to determine who first detected the illness sinusitis by obtaining data based on the effect from observations. PHP is the programming language used to create this Expert System application, and MySQL is the web-based database. In summary, this method is simple to use and build, and it might be helpful for anyone who are interested in learning more about sinusitis.